NGULAN MAPU (ARAUCANIA): THE ‘PACIFICATION’ AND ITS HISTORIOGRAPHICAL STORY, 1900 -1973. - León, Leonardo (Revista de Historia Social y de las Mentalidades, 2011)
This article analyzes the historiographic story abo ut mapuche’s lands occupation by the chilean Estate. The article is about recognize, cla rify and establish the paradigms that contaminates the transparency and lucidity of chile an historic conscience about mapuche people. Mainly , it requires review deeply the gnos eologic substrate on which is constructed our current view of an investigation and research t radition which was constructed without asking about the solidity of its bases, guiding its elf by the ideological lens of a time characterized by racism and social evolucionism.